The clinical implications of immunogenomics in colorectal cancer: A path for precision medicine. Issue 8 (9th January 2018) - Riley, Jenny M.; Cross, Ashley W.; Paulos, Chrystal M.; Rubinstein, Mark P.; Wrangle, John; Camp, E. Ramsay
Abstract : Colorectal cancer (CRC) remains the third most common malignancy and the second‐leading cause of cancer‐related deaths in the United States. Large multi‐omic databases, such as The Cancer Genome Atlas and the International Colorectal Cancer Subtyping Consortium, have identified distinct molecular subtypes related to anatomy. The identification of genomic alterations in CRC is now critical because of the recent success and US Food and Drug Administration approval of pembrolizumab and nivolumab for microsatellite‐instable tumors. In parallel, landmark studies have established the prognostic significance of the CRC tumor‐infiltrating lymphocyte and the clinical impact of the tumor immune microenvironment. As a result, there is a growing appreciation for immunogenomics, the interconnected relation between tumor genomics and the immune microenvironment. The clinical implications of CRC immunogenomics continue to expand, and it will likely serve as a guide for next‐generation immunotherapy strategies for improving outcomes for this disease. Cancer 2018;124:1650‐9 . © 2018 American Cancer Society Abstract : Colorectal cancer can be further defined at the genomic level and by the immunologic landscape; both allow better characterization of the tumor biology. This may serve to guide future immuno‐oncology precision medicine applications to improve outcomes for this disease.